Kenneth Peacock's Songs of the Newfoundland Outports CD-ROM - Peacock, Kenneth (SingSong Inc., 2000)
Kenneth Peacock's Songs of the Newfoundland Outports, 3 vols., on CD-ROM. -- "Collected between 1951 and 1961 by Kenneth Peacock, under the auspices of what was then the National Museum of Canada, this is the most comprehensive collection of traditional Newfoundland folk music ever complied. With over 500 songs in three volumes, it represents the single greatest contrbution to the preservation of Newfoundland folk song in any format." (case liner)